2020
DOI: 10.7759/cureus.7918
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia and Ageusia as the Only Indicators of Coronavirus Disease 2019 (COVID-19)

Abstract: The patient is a 60-year-old woman with a history of vertigo and seasonal allergies who presented to the hospital with the chief complaint of headache. Radiological findings were negative for intracranial abnormalities. The headache was due to trigeminal neuralgia. She had concurrent complaints of anosmia and ageusia without fever, respiratory symptoms, or obvious risk factors. However, it was determined to test the patient for coronavirus disease 2019 (COVID-19) infection despite extremely low clinical suspic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…Because the SARS-COV-2 pandemic has been a rapidly emergent phenomenon, there is a relatively low number of large-scale retrospective and observational studies reporting neuroradiological findings currently represented in the literature. Consequently, we decided to include 51 case reports and case series in this review for a total of 61 studies ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ) comprising 711 patients. All of these studies used a combination of CT and MRI, with the...…”
Section: Resultsmentioning
confidence: 99%
“…Because the SARS-COV-2 pandemic has been a rapidly emergent phenomenon, there is a relatively low number of large-scale retrospective and observational studies reporting neuroradiological findings currently represented in the literature. Consequently, we decided to include 51 case reports and case series in this review for a total of 61 studies ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ) comprising 711 patients. All of these studies used a combination of CT and MRI, with the...…”
Section: Resultsmentioning
confidence: 99%
“…The literature indicates that the most severe symptoms of the virus include respiratory distress, fever, cough and fatigue [ 39 , 48 ]. Other, less prevalent symptoms that may appear are diarrhea, nausea and vomiting [ 49 , 50 ]. Of the thirteen studies, only six reported individuals presenting changes in smell and taste who also experienced nasal obstruction [ 10 , 12 , 15 , 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…When established and severe, fulminant SARS-CoV-2 infection can rapidly evolve into a systemic illness characterized by hyper-inflammation, cytokine storm and rapid increase in systemic inflammatory biomarkers, elevations in cardiovascular malfunction and severe respiratory failure that is lethal in about 3% of all cases. Multiple neurological symptoms include loss of smell (anosmia), altered taste (ageusia), loss of the coordination of movement (ataxia), headache and nausea, dizziness, intermittent loss or impairment of consciousness, acceleration or aggravation of pre-existing cognitive deficits, direct negative effects of the heightened immune reaction, unusual hyper-inflammatory responses, increased vascular inflammation, inflammation of the brain and spinal cord and atherogenesis, exacerbation or de novo induction of inflammatory neurodegeneration, loss of respiratory control and progressive disturbances in cognition (Baig and Sanders 2020 ; Zhang et al 2020 ) including encephalitis (Efe et al 2020 ), stroke, seizures, encephalopathy (Zubair et al 2019 ) and acute disseminated encephalomyelitis (ADEM; Panupattanapong and Brooks 2020 ; Parsons et al 2020 ). One worrisome auxiliary sequela of CoV-19 infection called ‘multisystem inflammatory syndrome in children’ (MIS-C) has been observed in which children who have recovered from CoV-19 infection subsequently develop a severe inflammatory syndrome with Kawasaki disease-like features including persistent fever, conjunctivitis, hyper-inflammatory responses, elevated inflammatory markers and immunodeficiency, and a constellation of symptoms including hypotension, cardiac, gastrointestinal (GI), renal, hematologic, dermatologic and neurological involvement (Panupattanapong and Brooks 2020 ; Ronconi et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%